Analisa Unsharp Mask Filter Untuk Perbaikan Citra Pada Pas Foto - Sari, Dewi Purnama (STMIK Budi Darma, 2018)
Currently, the use of digital cameras to capture images or photos is more than using a manual camera with film media. This is because digital image retrieval has many advantages, especially in terms of storage which no longer uses physical media (film) but uses digital media and a very long storage age of images without reducing the quality of the image. One damage that might occur is the blurred image (blurred image). This damage can be caused by several things including the age of the photo that has been long, and wet with water. The thing that can be done to avoid the occurrence of blurred images caused by old photographs is to treat the image state. But in reality, it is very difficult to treat the condition of this image. Several methods have been developed to improve blurred images, including using the deconvolution process for kernel blur, unsharp mask. In this study, an application was developed to make improvements to the blurred image caused by the age of the old photo using the unsharp mask method. Unsharp mask is one of the digital image processing methods that can be used to reduce the level of image blur caused by photo age and image maintenance errors. Unsharp word naming is because this method uses a more blurry image of the original image as a mask-making factor. After the mask is obtained, the mask will be added to the original image so that the image is sharper than the original image.